High-Energy Extracorporeal Shock Wave for Early Stage Osteonecrosis of the Femoral Head: A Single-Center Case Series - Gao, Fuqiang (Evid Based Complement Alternat Med, 2015)
Our retrospective study assessed the effects of treatment of early stage ONFH with extracorporeal shock wave therapy. 335 patients (528 hips) were treated with shockwave therapy in our institution. Each patient underwent two sessions. The hips were divided into two groups according to whether the lateral pillar of the femoral head (LPFH) was preserved: LPFH and non-LPFH groups. Patients were followed up at 3, 6, and 12 months after the treatment. Most of the patients (83.9% hips) demonstrated pain reduction and improved mobility of the treated joint (visual analogue scale score, P = 0.00006; Harris hip score, P = 0.00091). During the follow-up period, 16 hips failed following femoral head collapse and required hip arthroplasty (2 hips in LPFH group and 14 hips in non-LPFH group). The lesion size decreased after ESWT. However, the differences were statistically not significant (LPFH group, P = 0.091; non-LPFH group, P = 0.087). A significant reduction in bone marrow edema was observed after treatment (LPFH group, P = 0.007; non-LPFH group, P = 0.016). High-energy extracorporeal shock wave therapy resulted in considerable improvement in early stage ONFH, which can effectively relieve pain and improve the function of the hip.